The Cook Islands, Niue and Tokelau as Parts of the Realm of New Zealand - Quentin-Baxter, Alison (Victoria University of Wellington Law Review, 2021)
The focus of This Realm of New Zealand by Alison Quentin-Baxter and Janet McLean was on the constitutional monarchy and its relationship with the laws of mainland New Zealand. This article complements This Realm of New Zealand by focusing on the constitutional monarchy and its relationship with other countries of the Realm of New Zealand – the Cook Islands, Niue and Tokelau.